2016
DOI: 10.1128/jvi.01001-16
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric and Cytokine ELISpot Approaches To Characterize the Cell-Mediated Immune Response in Ferrets following Influenza Virus Infection

Abstract: Influenza virus infections represent a significant socioeconomic and public health burden worldwide. Although ferrets are considered by many to be ideal for modeling human responses to influenza infection and vaccination, efforts to understand the cellular immune response have been severely hampered by a paucity of standardized procedures and reagents. In this study, we developed flow cytometric and T cell enzyme-linked immunosorbent spot (ELISpot) approaches to characterize the leukocyte composition and antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 87 publications
(83 reference statements)
2
39
0
Order By: Relevance
“…The staining and gating strategy is provided as Supplemental Figure 1. CD8 + T-cells were identified by gating on the CD8 + population with the highest mean fluorescence intensity (MFI) as this population had been shown to be the true CD8 + T-cell population15. In gating for the CD4 + T-cells, we had to account for the unexpectedly high background fluorescence of the IFNγ-PE and CD8-APC into the FITC-channel (see Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The staining and gating strategy is provided as Supplemental Figure 1. CD8 + T-cells were identified by gating on the CD8 + population with the highest mean fluorescence intensity (MFI) as this population had been shown to be the true CD8 + T-cell population15. In gating for the CD4 + T-cells, we had to account for the unexpectedly high background fluorescence of the IFNγ-PE and CD8-APC into the FITC-channel (see Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We did not detect any significant CD4 + T-cell numbers in the BALF and the numbers were highly varied in the peripheral blood, particularly for the ferrets in the naïve group with more severe disease. A study published recently15 reported an average of 40% CD4 + and 15% CD8 + T-cells in the BALF of two ferrets infected with the H1N1 virus at day 10 post-infection. Whether the early time-point and the rapidly declining health of our ferrets, or a suboptimal detection antibody, confounded our ability to reliably detect the CD4 + T-cells, is uncertain.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, an infiltration of CD11b+ and MHC‐II+ cells into lungs between 2 and 5 d.p.i was observed, which could represent lung APCs . CD11b+ cells also increase in secondary lymphoid organs 10 d.p.i, suggesting a coordinated immune response involving both innate and adaptive responses to resolve infection.…”
Section: Ferrets As An Immunological Model For Studying Influenzamentioning
confidence: 93%
“…In the absence of cross‐reactive clones, several groups have generated novel monoclonal antibodies specific for ferret cellular markers. For example, novel anti‐ferret CD4‐, CD8‐ and CD5‐specific antibodies were derived by immunising mice with the CD4 ectodomain, whole CD4 protein or ferret thymocytes . Efforts to develop novel antibody‐based reagents to define various ferret immune cell subpopulations are accelerating, particularly through the Centers of Excellence for Influenza Research and Surveillance (CEIRS) network, and are reviewed in detail further below.…”
Section: Ferrets As An Immunological Model For Studying Influenzamentioning
confidence: 99%
See 1 more Smart Citation